Influential factors associated with core competencies of diabetes specialist nurses and correlation with self‐directed learning ability: A cross‐sectional study - Yuan Gao; Min Zhou; Yan Yan Liu; Jun Yang Ma; Pei Shan Tian; Man Fen Qin (Wiley, 2024)
Abstract Aims and Objectives This study aimed to investigate the current status of the core competencies and self‐directed learning ability of diabetes specialist nurses and to explore the relationship between these core competencies and their self‐directed learning ability. Design A cross‐sectional survey design was used. Methods This cross‐sectional study was conducted via a web‐based questionnaire platform in China from January 14 to April 24, 2023. The survey included a general information questionnaire, a diabetes specialist nurses' core competencies self‐assessment scale, and a nursing staff's self‐directed learning ability evaluation scale. The data was collected online. Descriptive, correlation and multiple linear regression analyses were conducted using SPSS 26.0 software. Results 118 diabetes specialist nurses from 11 cities participated in this study. A positive correlation was observed between the core competencies of diabetes specialist nurses and their self‐directed learning ability. The characteristics affecting the core competencies of diabetes specialist nurses included age, participation in external learning and communication and self‐directed learning. Conclusions The training of diabetes specialist nurses can focus on core competencies, and the ability to self‐direct learning can be used as an entry point to customize feasible theoretical and practical courses. The training system can further improve diabetes specialist nurses' core competencies and self‐directed learning abilities. Relevance to Clinical Practice A reference can be established that nursing managers and nursing educators can use to develop training programs for specialist nurses by validating the link between their core competencies and self‐directed learning skills. Patient or Public Contribution Participants were involved solely in the data collection process. No participant contributions were required for the study's design, outcome measurement or implementation.